Influence of Financial Literacy on MSME Performance with Financial Inclusion as a Mediation - Siti Barokah; Muhammad Sayyid Candivas; Nia Nurani; Keyzha Lungguh Arta Nugraha (ICON Publisher, 2024)
The role of Micro, Small, and Medium Enterprises (MSMEs) is very fundamental as a pillar of the Indonesian economy. This study examines the effect of financial literacy on the performance of MSMEs with financial inclusion as a mediating variable conducted on MSMEs in Wero Village. The study focused on 40 MSME actors who were sampled. Questionnaires were given to respondents to obtain accurate data. Data analysis was carried out using the Partial Least Square (PLS) method with SmartPLS 3.0 software. The results of the study showed that financial literacy did not have a positive and significant effect on MSME performance. However, financial literacy has a positive and significant effect on financial inclusion which is then proven to be effective as a mediator in the positive relationship between financial literacy and MSME performance. This study still has limitations, namely only examining MSMEs in Wero Village. So further research is needed so that the findings can be generalized.